Identification of Coastal Mangroves in the Legend Ecotourism Pademawu District Pamekasan Regency: an Explorative Descriptive Study - Minhatul Muyassaroh; Lukluk Ibana; Linda Tri Antika (Indonesian Journal of Biology Education, 2023)
Mangrove inventory is important for monitoring and supporting building mangrove management strategies in the future. Until now, there has been no data collection on what types of mangroves grow in the coastal area of The Legend Pademawu. This study aims to record what types of mangroves exist in the area. Data on mangrove species were collected using exploratory descriptive methods. The results showed that mangroves found in the coastal area of The Legend Padelegans Village, Pademawu District, Pamekasan Regency amounted to 11 species grouped into 7 families. Most mangrove species are dominated by the Rhizoporaceae family which amounts to 3 species. Following up on the findings in this study, in the future it is necessary to carry out mangrove ventilation for monitoring and supporting in building mangrove management strategies in the future.